Energy Transition and Sustainability in the United Kingdom: A Systematic Review under the PRISMA Guidelines - Sauna-Aguilar, Brayan; Vega-Solis, Edwin; Díaz-Matienzo, Nayeli; Mendoza-Vasquez, Ari; Paico-Egusquiza, Ayle (International Journal of Energy Economics and Policy, 2025)
In the energy transition, environmental sustainability has led to the development of new renewable energies, such as tidal energy, which generates continuous and predictable electricity from ocean tides. This study conducts a Systematic Literature Review (SLR) according to the PRISMA 2020 method, focusing on the implementation and technological development of tidal energy. A quantitative approach was used to analyze 37 studies from 2020 to 2024 in Scopus. The results show the use of key tools such as the 0-D model, TPXO9, and the acoustic doppler current profiler (ADCP) to optimize this renewable source. The TPXO9 model stands out for its accuracy in predicting tides, assisting in infrastructure planning and energy efficiency. The United Kingdom leads the development of tidal energy, promoting innovative research and projects. The review highlights the importance of this renewable energy in reducing dependence on fossil fuels and carbon emissions, serving as a basis for future research and the advancement of the energy transition towards green production and environmental sustainability.